Evaluation of Irrigation Water Application Techniques at Omo Kuraz Left Bank Canal, SNNPRE, Ethiopia - Firdawek Zewudu Shibeshi; Tamene Mojira Mogiso; Yilkal Zewude Eniyew (Indonesian Journal of Earth Sciences, 2023)
Water loss from furrows can be due to runoff, seepage and deep percolation which may cause yield reduction. This study focuses on the evaluation of irrigation water application techniques and employed experimental observation which included 30 test observations using the bund, cut-off, cut-back, surge, and portable structure techniques. The experiments were carried out in two blocks; block A with 50 m furrow length and that of block B with 100 m furrow length. The experimental design was a randomized complete block design with three replications. The analysis was done using surface irrigation evaluation model and SAS software package. The results of the study showed that at block A, highest application efficiency of 87.0% was obtained with surge flow and followed to this cut-back recorded 86.6%; whereas the lowest application efficiency of 75.00% was obtain by bund technique. Storage efficiency of surge and cut-back recorded 99.00%. The lowest was obtained by bund (88.9%). The distribution uniformity of surge was highest (84.1%). whereas bund technique gave 71.0% of lowest distribution efficiency. At block B, surge registered the highest application efficiency and distribution uniformity of 66.0% and 59.57% whereas; bund technique records the lowest application efficiency of 60%. The surge and cut-back were more efficient in the field recovery of storage requirement resulted above 99.0%. The statistical analyzed results showed that mean application efficiency of 75.69% was obtained using the surge technique; whereas the lowest application efficiency of 70.0% was obtained by the bund. The use of the surge technique reduces irrigation water loss from 30.0% to 24.3% compared to the local bund technique. This is due to the surge performed better in terms of advance rate and efficient moisture content. With the surge, the highest mean DU of 68.07 % was obtained, while the bund technique had the lowest DU (58.32%). Therefore, adoption of the surge is a promising water application and management practice in sugar cane plantation at Omo Kuraz.